Inhibition of aluminium corrosion using phthalocyanines: Experimental and computational studies - Nnaji, Nnaemeka Joshua (Rhodes University, Faculty of Science, Department of Chemistry)
Metal deterioration over time is a process known as corrosion, an electrochemical process, which can occur by surface chemical actions on metals by its environment. Metal corrosion have great economic, security, and environmental consequences, and its control is a major research area in corrosion science. Amongst the different corrosion protecting approaches, the use of corrosion inhibitors and protective coatings have attracted enormous research interest in this area of scholasticism. This has necessitated the computational and electrochemical investigations of aluminium corrosion inhibitive potentials of some compounds in 1M HCl. Metal free (5_H2), ClGa(III) (5_Ga) and Co(II) (5_Co) tetrakis(4-acetamidophenoxy)phthalocyanines as well as Co(II) 2,9,16-tris(4-(tert-butyl)phenoxy)-23-(pyridin-4-yloxy)phthalocyanine (6) and Co(II) 2,9,16,24-tetrakis(4-(tert-butyl)phenoxy)phthalocyanine (7) were synthesized for the first time and studied for corrosion inhibition. The reported ClGa(III) tetrakis(benzo[d]thiazol-2-yl-thio)phthalocyaninine (1), ClGa(III) tetrakis(benzo[d]thiazol-2ylphenoxy)phthalocyanine (2), ClGa(III) tetrakis-4-(hexadecane-1,2-dioxyl)-bis(phthalocyanine) (3) and ClGa(III) tetrakis-4,4"²-((4-(benzo[d]thiazol-2-yl)-1,2-bis(phenoxy)-bis(phthalocyanine) (4) were also employed for corrosion inhibition of Al in HCl. Corrosion inhibition measurements using electrochemical techniques showed that increased Ï€ conjugation caused (1) to (2) to outperform (1a) and (2a) respectively as aluminium corrosion inhibitors in 1.0 M hydrochloric acid. For similar reason, (4) outperformed 2. (1) and (2) were successfully electrodeposited onto aluminium for corrosion retardation in 1.0 M hydrochloric acid solution. Measurements obtained from electrochemical impedance spectroscopy gave corrosion inhibition efficiency values of 82% for 1 and 86% for 2 in 1.0 M hydrochloric acid solution and showed that electrodeposited phthalocyanines have enhanced aluminium corrosion retardation than when in solution. The use of reduced graphene oxide nanosheets (rGONS) alone as aluminium corrosion inhibitor is discouraged because of poor aluminium corrosion inhibition in 1M HCl. However, synergistic effects were observed when rGONS was mixed each with (4) and (3). (5_H2), (5_Ga) and (5_Co) decreased aluminium corrosion in 1M HCl and observation was that the heavier the atom the more decreased the protection and the free base performed best of the three. Studied tertbutylphenoxy-derived CoPcs (6 and 7) exhibited good aluminium corrosion inhibition properties in studied acidic solution and the unsymmetric CoPc (6) which has more heteroatoms, gave better performance. Quantum chemical calculations involved the use of density functional theoretical (DFT) approaches and gave results which corroborated with experimental findings.
Keywords: Aluminum -- Corrosion; Electrochemistry; Phthalocyanines; Corrosion and anti-corrosives; Protective coatings; Density functionals